Net investment position and the stock market: The case of traditional and ESG indices - Jaroslav Slepecký (Investment Management & Financial Innovations, 2022)
This paper explores the influence of traditional and ESG stock market indices on a country’s net international investment position. To do this, different methods, including ANOVA analysis, multiply regression analysis, correlation analysis, VAR-analysis and R/S-analysis, as well as the Granger causality test, are applied to quarterly data on the net international investment position, traditional and ESG indices from Finland, Sweden, France, Spain and Ukraine over the period 2005–2021. The results of descriptive statistics show that ESG indices are more volatile than traditional, but these differences are statistically insignificant according to ANOVA analysis. Correlation analysis provides direct evidence that ESG indices are highly correlated with their traditional analogues (correlation level varies from 0.88 to 0.96). Regression analysis results show that traditional and ESG stock market indices have no significant impact on the net international investment position. ESG stock market indices and net international investment position data are persistent, and autoregressive models can be applied to these data sets. On average, Hurst exponent is above 0.75 for the case of ESG indices and above 0.85 for the net investment position. This paper provides recommendations to improve the responsible investment framework. Acknowledgment Alex Plastun gratefully acknowledges financial support from the Ministry of Education and Science of Ukraine (0121U100473).